2019
DOI: 10.1101/526038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecological specificity of the metagenome in a set of lower termite species supports contribution of the microbiome to adaptation of the host

Abstract: nutrients from more diverse sources. This supports the idea that specific subsets of functions encoded by the microbiome can contribute to host adaptation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…This study is the first to clearly demonstrate the existence of urate oxidase in termites. Previously, it was believed that termites lack this enzyme in their tissues, instead completely relying on symbiotic microbes in their hindguts for uric acid degradation [8,[12][13][14][15]. We also showed that uric acid degradation by urate oxidase is the key to reproduction in termites.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…This study is the first to clearly demonstrate the existence of urate oxidase in termites. Previously, it was believed that termites lack this enzyme in their tissues, instead completely relying on symbiotic microbes in their hindguts for uric acid degradation [8,[12][13][14][15]. We also showed that uric acid degradation by urate oxidase is the key to reproduction in termites.…”
Section: Discussionsupporting
confidence: 51%
“…ammonia) [8,[12][13][14][15]. However, termites cannot access the nutritionally useful metabolites produced in the hindguts without trophallaxis [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not perform a temporal study, the differences in bacterial diversity were observed after 18 days of exposure to new diets. Higher microbial diversity is expected in UNX since termites in their natural habitat forage different food sources and acquire new microorganisms as well as micronutrients from soil [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbes are important drivers of host phenotype and evolution [1]. Benefits derived from microorganisms can facilitate the occupation of new ecological niches [2][3][4][5] and microbial effects on host phenotypes and fitness can spur adaptive processes [6][7][8][9][10][11][12][13][14]. Changes in the effects of microbes on host fitness can alter interactions along the parasitism mutualism continuum [6,[15][16][17][18], thus affecting the evolutionay trajectories of the partners.…”
Section: Introductionmentioning
confidence: 99%